Details of the Vedibandha of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The kumbha (pot) molding of the vedibandha (basal mouldings) stands out due to its depiction of divine figures within the niches, featuring gods and goddesses like Kubera, the deity associated with wealth. Notably, the top of the kumbha is adorned with a chaitya arch, a feature commonly found on kapotapalika (cyma recta) moldings. Below the kumbha, there is a band showcasing kirtimukha (face of glory) motifs, while above the kumbha, the molding of kalasha (pitcher) is intricately carved with ratnapatta motifs.